Systems of power and citizenship in the U.S. 2010 Foreign Intelligence Surveillance Act - Doggett, Katherine, author; Dickinson, Greg, advisor; Gibson, Katie, committee member; Hallahan, Kirk, committee member (Colorado State University. Libraries, 2015)
In 1978, the United States government developed the Foreign Intelligence Surveillance Act (FISA) to guide how the U.S. government conducts intelligence-gathering operations on individuals located outside of the United States—a piece of legislation that has been amended throughout the years, yet its 2010 version remains in effect today. Using Foucault’s concept of power/knowledge and literature on citizenship, this study explores the power relationships and subjectivities that are produced within the rhetoric of FISA. Ultimately, I argue that the rhetoric of FISA creates the subject of person as citizen, and citizens as inscribed within a broader structure of national power. Citizens of the United States are granted unmatched privacy rights and legal protections, and non-U.S. individuals are bound as quasi-citizens: possessing duties to the U.S. while receiving diminished rights in return. Implications for surveillance, personhood, and foreign policy are discussed.
Keywords: FISA; personhood; surveillance; foreign; citizenship; power/knowledge